2013
DOI: 10.1093/nar/gkt367
|View full text |Cite
|
Sign up to set email alerts
|

Polycomb recruitment attenuates retinoic acid–induced transcription of the bivalent NR2F1 gene

Abstract: Polycomb proteins play key roles in mediating epigenetic modifications that occur during cell differentiation. The Polycomb repressive complex 2 (PRC2) mediates the tri-methylation of histone H3 lysine 27 (H3K27me3). In this study, we identify a distinguishing feature of two classes of PRC2 target genes, represented by the Nr2F1 (Coup-TF1) and the Hoxa5 gene, respectively. Both genes are transcriptionally activated by all-trans retinoic acid (RA) and display increased levels of the permissive H3K9/K14ac and tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 69 publications
2
54
0
1
Order By: Relevance
“…On a molecular level, RA mediates major changes in epigenetic marks on specific target genes (33)(34)(35)(36)(37). We recently showed that Stra6 transcripts are increased by RA treatment of embryonic stem (ES) cells and that this induction depends on RAR␥ (38).…”
mentioning
confidence: 99%
“…On a molecular level, RA mediates major changes in epigenetic marks on specific target genes (33)(34)(35)(36)(37). We recently showed that Stra6 transcripts are increased by RA treatment of embryonic stem (ES) cells and that this induction depends on RAR␥ (38).…”
mentioning
confidence: 99%
“…44 Retinoic acid signaling induces optic vesicle and brain development and Nr2f1 and Nr2f2 transcription in mice stem cells. 45 These findings indicate that RERE is a likely candidate gene for CVI (http://www. REREgene.com).…”
Section: Resultsmentioning
confidence: 95%
“…In neuroblastoma cells, RA induced neural maturation through RET gene transcriptional activation by increasing H3K4me3 levels at the promoter region and demethylating H3K27me3 at an enhancer region [13]. Furthermore, during RAinduced F9 cell differentiation, Nr2f1 and Hoxa5 are transcriptionally activated by RA and display increased levels of the permissive H3K9/K14ac and H3K4me3 epigenetic marks [14]. These studies suggest that RA can regulate gene expression by alteration of histone modifications in different cells.…”
Section: Introductionmentioning
confidence: 76%